Constraint Induced Movement Therapy Camp for Children with Hemiplegic Cerebral Palsy Augmented by Use of an Exoskeleton to Play Games in Virtual Reality. (4th September 2020) - Roberts, Heather; Shierk, Angela; Clegg, Nancy J.; Baldwin, Deborah; Smith, Linsley; Yeatts, Paul; Delgado, Mauricio R.
Abstract: Aim: To determine the acceptability and effects of a pediatric constraint induced movement therapy (P-CIMT) camp for children with hemiplegic cerebral palsy (hCP) augmented by use of an exoskeleton to play games in virtual reality (VR). Method: 31 children with hCP attended a P-CIMT camp 6 hours per day for 10 days over 2 successive weeks (60 hours) that included 30 minutes of unilateral training with the Hocoma Armeo ® Spring Pediatric that combines the assistance of an exoskeleton and VR games. The primary outcome measure was the Assisting Hand Assessment (AHA); secondary outcome measures were the Melbourne Assessment of Uni-lateral Hand Function (MUUL), and the Canadian Occupational Performance Measure (COPM). Assessments were completed at pre-intervention, post-intervention, and 6 months following intervention. Results: Participants demonstrated clinically and statistically significant improvement in bimanual performance (AHA) ( p < .001) and COPM Performance ( p < .001) and Satisfaction with performance ( p < .001). Improvement in unilateral performance (MUUL) was statistically ( p < .001) but not clinically significant. Conclusions: A P-CIMT camp augmented by the Hocoma Armeo ® Spring Pediatric was feasible and accepted by participants. Bimanual hand function and occupational performance improved immediately following intervention, and the treatment effects persisted 6 months following intervention.